Effect of Water and Alcohol Extracts of Myrtus communis and Camellia sinensis in the Growth and Efficacy of Pseudomonas aeruginosa Bacteria and Escherichia coli Bacteria - Raad Abdul Hadi Nyif (Al-Mustansiriyah Journal of Science)
Abstract